Changing respiratory expectations with the new disease trajectory of nusinersen treated spinal muscular atrophy [SMA] type 1. (September 2018) - Fitzgerald, Dominic A.; Doumit, Michael; Abel, Francois
Summary: Spinal muscular atrophy [SMA] is the most common genetic cause of childhood mortality, primarily from the most severe form SMA type 1. It is a severe, progressive motor neurone disease, affecting the lower brainstem nuclei and the spinal cord. There is a graded level of severity with SMA children from a practical viewpoint described as "Non-sitters", "Sitters" and less commonly, "Ambulant" correlating with SMA Type 0/Type 1, Type 2 and Type 3 respectively. Children with SMA Type 0 have a severe neonatal form whilst those with SMA Type 1 develop hypoventilation, pulmonary aspiration, recurrent lower respiratory tract infections, dysphagia and failure to thrive before usually succumbing to respiratory failure and death before the age of 2 years. The recent introduction of the antisense oligonucleotide nusinersen into clinical practice in certain countries, following limited trials of less than two years duration, has altered the treatment landscape and improved the outlook considerably for SMN1 related SMA. Approximately 70% of infants appear to have a clinically significant response to nusinersen with improved motor function. It appears the earlier the treatment is initiated the better the response. There are other rarer genetic forms of SMA that are not treated with nusinersen. Clinical expectations will change although it is unclear as yet what the extent of response will mean in terms of screening initiatives [e.g., newborn screening], "preventative strategies" to maintain respiratory wellbeing, timing of introduction of respiratory supports, and prolonged life expectancy for the subcategory of children with treated SMA type 1. This article provides a review of the strategies available for supporting children with respiratory complications of SMA, with a particular emphasis on SMA Type 1.